REVOLUSI MORAL MELALUI PENERAPAN PROGRAM TAHFIDZ AL-QUR’AN DI MIN 2 OKU TIMUR - Tri Ratna Dewi; Resti Septikasari; Nor Kholidin; Imam Rodin; Defi Fitriyeni (Fitrah, 2023)
Learning Tahfidz Al-Qur’an is a superior program from Madrasah institutions. One of the aims of implementing the tahfidz Al-Qur’an program is to shape the morale of students. This research aims to obtain data/information related to how the implementation of the Al-Qur’an tahfizd program is managed at MIN 2 OKU Timur, both in terms of planning, implementation and evaluation that have been established at MIN 2 OKU Timur, apart from that it also looks at how the values moral values ​​possessed by students at MIN 2 OKU Timur. The planning carried out in implementing the tahfidz program at MIN 2 East OKU is designing a schedule and curriculum for learning tahfidz al-Qur’an. The implementation of the tahfidz program at MIN 2 OKU Timur is carried out every day in the hours before learning with a lesson time of 1 hour (35 minutes). There are 2 types of evaluation, namely daily evaluation and final letter evaluation. And evaluation Evaluation of character improvement is held once a month with each ustadz/class teacher submitting a summary of the results of observations of student behavior while participating in tahfidz activities.